VERTIGO IN MULTIPLE MYELOMA PATIENT: A CASE REPORT - Rangga Wisnu Wardhana (Faculty of Medicine Universitas Kristen Duta Wacana, 2019)
Background: Multiple myeloma is caused by pathological proliferation and inhibition of apoptosis of plasma cells inside bone marrow. There are several mechanisms which explains neurologic manifestations (peripheral and central) of multiple myeloma, such as neurologic infiltration, gamma globulin deposits, and metabolic changes. Aim: To describe vertigo syndrome in a multiple myeloma patient admitted to Sardjito Hospital. Case Description: A male, 60 years old, admitted to Sardjito hospital for severe dizziness in the past 24 hours before admission. This dizziness ameliorated after adequate rest. The patient experienced nausea and vomiting which was not worsen by positional changes. He was diagnosed with multiple myeloma since December 2015. The physical examination showed normal vital sign, without nystagmus. He showed an intentional tremor, dysdiadochokinesia, and dysmetria. The laboratory examination revealed anaemia, hypoalbuminemia, hyponatremia, and hyperglycaemia. Chest x-ray showed pulmonary infiltration on all lobes, with suspected osteoclastic bone metastases at left and right scapula, and the 11th right costae. Non-contrast head CT scan showed an osteoblastic skeletal metastatic at 3rd cervical vertebra. Audiometry with BERA indicated a bilateral peripheral lesion. The symptoms improved with flunarizine and diphenhydramine. Conclusion: Mixed central and peripheral vertigo is one of severe systemic manifestation of multiple myeloma.